Life history and narrative - Hatch, J. Amos; Wisniewski, Richard (Qualitative studies series, 1995)
"This book collects in one volume a number of cutting-edge essays that represent the best work being done at present in the emerging field known as life history and narrative inquiry. Authors include scholars from a variety of disciplines and perspectives within the social sciences who are recognised as leaders in the development of this research genre. The audience for the book includes social science scholars and graduate students involved in qualitative research methodologies in general, and narrative and life history methods and ethics in particular. Topics addressed include: qualitative analyses of narrative data; criteria for evaluating narrative inquiry; linking emotion and reason through narrative voice; audience and politics of narrative; trust in education storytelling; narrative strategies for case reports; life history narratives and women's gender identity; and issues in life history and narrative inquiry. Together these essays lift the whole field to the next level of understanding and debate."--Jacket